Application of the strip clear-cutting system in a running bamboo (Phyllostachys glauca McClure) forest: feasibility and sustainability assessments - Liang, Kuan; Wang, Guangru; Shen, Zhan; Wu, Juan; Zou, Na; Yu, Hongying; Yu, Shebao; Chen, Fusheng; Shi, Jianmin (Frontiers in Plant Science, 2024)
As a renewable forest resource, bamboo plays a role in sustainable forest development. However, traditional cutting systems, selection cutting (SeC) and clear-cutting (ClC), result in an unsustainable production of bamboo forests due to labor-consuming or bamboo degradation. Recently, a strip clearcutting (StC) was theoretically proposed to promote the sustainability of bamboo production, while little is known about its application consequence. Based on a six-year experiment, we applied the strip clear-cutting system in a typical running bamboo (Phyllostachys glauca McClure) forest to assess its feasibility and sustainability. Using SeC and ClC as control, we set three treatments with different strip widths (5 m, 10 m and 20 m) for strip clear-cutting, simplified as StC-5, StC-10 and StC-20, respectively. Then, we investigated leaf physiological traits, bamboo size and productivity, population features and economic benefits for all treatments. The stand biomass of StC (8.78 t hm -2 year -1 ) was 1.19-fold and 1.49-fold of SeC and ClC, respectively, and StC-10 and StC-20 were significantly higher than SeC or ClC (p < 0.05). The income and profit increased with the increase in stand density and biomass, and StC-20 and StC-10 were significantly higher than SeC or ClC (p < 0.05). Using principal components analysis and subordinate function analysis, we constructed a composite index to indicate the sustainability of bamboo forests. For the sustainability assessment, StC-10 owned the highest productive sustainability (0.59 ± 0.06) and the second highest economic sustainability (0.59 ± 0.11) in all cutting treatments. The maximum overall sustainability appeared in StC-10, with a value of 0.53 ± 0.02 and significantly higher than ClC (p < 0.05). The results verified that StC for Phyllostachys glauca forests is feasible and sustainable as its sustainability index outweighs the traditional cutting systems (SeC and ClC), and 10 m is an optimum distance for the strip width of StC. Our findings provide a new cutting system to manage other running bamboo forests sustainably.